1988
DOI: 10.1007/bf01741418
|View full text |Cite
|
Sign up to set email alerts
|

Problems of fibrin adhesion of the nerves

Abstract: Although the fibrin adhesion enjoys increasing success in many areas of surgery, it has not, however, become fully established in nerve anastomosis. It was in this area particularly that significant advantages were expected. As the fibrin clot dissolved prematurely, however, and dehiscences ensued, antifibrinolytic substances had to be added to the adhesive. Fibroses occurred frequently as a result, which to date encumber nerve adhesive. We examined various factors of the adhesive system for their fibrosis-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 55 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Measurement of repair site nerve diameter and collagen thickness was performed to assess scar tissue formation and potential nerve compression as described by similar reports making observations on nerve fibrosis[ 10 , 21 ]. Though the nerves were not stretched, slides were prepared as consistently as possible between the two groups with regards to avoiding undulation and comparing equivalent samples though perfect standardization could not be guaranteed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of repair site nerve diameter and collagen thickness was performed to assess scar tissue formation and potential nerve compression as described by similar reports making observations on nerve fibrosis[ 10 , 21 ]. Though the nerves were not stretched, slides were prepared as consistently as possible between the two groups with regards to avoiding undulation and comparing equivalent samples though perfect standardization could not be guaranteed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, one criticism of the use of fibrin glues in general is that they may generate excessive scar tissue. Herter found that multiple components found in fibrin glue all actually induced fibrosis[ 10 ]. PEG hydrogel, on the other hand, has been shown to inhibit adhesion formation in a rabbit pericardial abrasion model[ 29 ], a canine durotomy repair model[ 15 ], and a porcine intra-abdominal adhesion model[ 14 ].…”
Section: Discussionmentioning
confidence: 99%